The Encyclopedia of Biology - Rittner, Don and McCabe, Timothy Lee (New Dehli Viva Books, 2016)
Presents approximately 800 alphabetical entries and essays on topics in biology, including line illustrations and black-and-white photographs.
Includes Appendix, Illustrations and Index.
Keywords: Biology -- Encyclopedias